Increased biodegradability of the fungicide imazalil after photo-Fenton treatment in solar pilot plant. Issue 2 (April 2019) - Loveira, Elsa López; Fantoni, Sofia; Espinosa, Mariela; Babay, Paola; Curutchet, Gustavo; Candal, Roberto
Graphical abstract: Highlights: Solar photo-Fenton increased biodegradability of solutions containing imazalil and coadjuvants. COD and TOC of the pre-oxidized solutions decreased notably during the biotreatment. H2 O2 efficiency as oxidant increased when it was incorporated in doses during solar photo-Fenton. Coupled solar photo-Fenton – biotreatment can be used in latitudes as high as -34.5 °. Abstract: Wastewater containing pesticides released to water courses without any previous treatment produces an extremely negative impact into the environment, causing concern among the population and authorities. Imazalil (IMZ) is a post-harvest fungicide used on a myriad of fruit crops; it is classified as "likely to be carcinogenic in humans" and produce a negative impact on the biota. In this work we propose a coupled solar Fenton-Biological process in a pilot plant for the treatment of water containing the fungicide IMZ and organic coadjutants. Water solutions containing up to 500 mg/L IMZ, 500 mgC/L TOC and 1300–1400 mgO2 /L COD were partially oxidized by Solar-Fenton process. For the first time, the efficiency of the treatment in the Buenos Aires area during different seasons was studied. In summer the treatment was faster but less efficient than in winter. Organic compounds were converted to organic acids like malic, formic and oxalic acids. The resultant solution was biodegraded using consortium adapted to IMZ oxidation byproducts without the incorporation of any extra carbon sources. As a result of the treatment TOC and COD were reduced to acceptable values for discharge in sewage, and its toxicity (determined by assays on Lactuca sativa L.) was significantly decreased. These results exemplified the advantages of combining advanced oxidation with the biological process for recalcitrant compounds degradation.